Overview of Risk Factors in Hypertension Disease - Niken Nurul Hanifah; Tintin Sumarni; Desi Deswita; Deharnita; Anita Mirawati; Aini Yusra (Journal of Applied Holistic Nursing Science, 2025)
Background : Hypertension can generally be defined as systolic pressure of more than 140 mmHg and diastolic pressure of more than 90 mmHg. Human blood pressure naturally fluctuates throughout the day. Modifiable risk factors are (salt consumption, obesity, physical activity, smoking, stress). The purpose of this study was to determine the Description of Risk Factors in Hypertension Disease. Methods: The research design used is descriptive of the Tanjung Paku Health Center Working Area, Solok City in 2024, in March - April 2024, data was collected from March 25 to April 6, 2024, the population was hypertensive patients in the Tanjung Paku Health Center Working Area, Solok City. The sample was taken by accidental sampling, formulating the sample with the slovin formula with a total of 55 respondents. Data was taken by filling out a questionnaire with respondents and observation. Results: The results of the study obtained from the description of risk factors for hypertension showed that 45 (81.8%) respondents consumed 1 teaspoon of salt per day, 36 (65.5%) respondents were not obese, 31 (56.4%) respondents did not do physical activity, 43 (78.2%) respondents did not smoke, 54 (98.2%) respondents experienced mild stress. Conclusion: Hypertension risk factors include salt consumption, obesity, lack of physical activity, smoking, and mild stress, which can increase the risk of complications.